The application of set-based concurrent engineering to enhance the design performance of surface jet pump - Mohd Maulana, Muhd Ikmal; Flisiak, Jakub Wiktor; Al-Ashaab, Ahmed; Araci, Zehra Canan; Lasisz, Piotr Wojciech; Beg, Najam; Rehman, Abdullah (World Scientific and Engineering Academy and Society (WSEAS), 2016)
Set-Based Concurrent Engineering (SBCE) is an approach that has the capability to improve the efficiencies of the product development process. SBCE provides an environment where design space is explored thoroughly which lead to enhance innovation. This is achieved by considering an alternative set of solutions after gaining the right knowledge to support decision to narrow down the set of solutions until the single optimal design solution is reached. This paper presents a novel application SBCE in order to generate alternative design to enhance the efficiency of the Surface Jet Pump (SJP) in term of its productivity and performance of producing the oil and gas in oil and gas well.
Keywords: lean product development; set-based concurrent engineering; product development; set-based design; trade-off curve; surface jet pump